Persiapan Generasi Religius, Cerdas, Berkarakter, Melalui Workshop Program Parenting Berbasis Keluarga Di Desa Telukambulu – Kecamatan Batu Jaya – Kabupaten Karawang - Faizin, Muhamad; Saprialman; Fahmi, Ilham; Nurhasan; Novian M, Mohammad Aidil; Syifana, Mutiara (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
The family is the first school for every individual born into this world; therefore, instilling educational values should naturally begin within the family environment. This workshop program aims to enhance parents' awareness and understanding of family education and to create a healthy, supportive, and conducive environment for the optimal development of children in Telukambulu Village, Batu Jaya Subdistrict, Karawang Regency. This village was selected based on the evident need for parenting education that directly engages the community. Through family-based parenting workshops, this program focuses on shaping a generation that is religious, intelligent, and of strong character through a holistic and integrated approach. The program involves collaboration with local religious institutions such as mosques, Majelis Taklim, and community organizations to ensure its sustainability and relevance. Five strategic steps are undertaken, including: 1) Collaboration with local religious institutions, 2) Designing parenting programs tailored to the culture and understanding of the local community, 3) Integrating character values such as honesty, discipline, and responsibility into daily family life, 4) Promoting literacy and formal education as part of developing an intelligent generation, and 5) Encouraging active parental involvement in educating children through positive parenting practices. The outcomes of this workshop program not only include the formation of a generation that is religious, intelligent, and of strong character but also a reduction in juvenile delinquency through the application of religious and moral values. By strengthening moral foundations, children are expected to overcome social pressures and make appropriate decisions, contributing to their mental and emotional well-being while improving family harmony. The outputs of this program include scientific articles published in Sinta-indexed national journals, activity videos, articles in print media, and relevant Intellectual Property Rights (IPR) products. In conclusion, many parents still raise their children using traditional parenting methods, while today’s Gen-Z children require adjustments in parenting approaches to ensure proper guidance and education for their future. Thus, this workshop serves as a means of providing understanding and literacy for parents in raising their children effectively.